(untitled) (Physical Education, Health and Social Sciences, 2025)
The study was conducted to evaluate the effectiveness of chemical and botanical insecticides against major cabbage insects at farmer field, District Dadu, Sindh during September-December 2023. Green Light” variety was sown in the first week of September, and the nursery was transplanted into the field during the first week of October. Seven treatments were applied including control viz., 10% Tobacco leaves extract, 10% Chinaberry fruit extract, 10% Neem leaves extract, Lambda cyhalothrin 2.5 EC, Imidacloprid 25% WP and Spinosad 240 SC, replicated 3 times. An untreated control plot was left blank as a check plot. Randomize Complete Block Design (RCBD) and Statistix 8.1 was used for analysis. Results show that all the tested treatments were found to be better than the control in reducing the cabbage larvae population. Spinosad 240 SC was found to be the most effective treatment with the lowest larvae population (0.89 and 0.77 larvae leaf-1) and maximum reduction of larvae population (73.04 and 84.01 %) after 1st and 2nd treatment application, respectively. Among botanical extracts, Neem leaf extract was the most effective, with the lowest larval population (1.18 and 1.04 larvae leaf-1) and the highest reduction (57.30% and 75.36%) after the 1st and 2nd treatment applications. The tested treatments were also found to be better than the control in reducing cabbage aphids’ population. Spinosad 240 SC was found the most effective treatment with the lowest aphids population (4.69 and 2.47 aphids leaf-1) and maximum reduction of aphid population (60.97 and 80.31 %) after 1st and 2nd treatment applications, respectively. Compared to other botanical extracts, Neem leaf extract showed the lowest aphid population (6.14 and 3.90 per leaf) with percent mortality of 48.74% and 68.00% after the 1st and 2nd applications. Resulting in the highest yield of cabbage (1005.33 kg ha-1) with cost-benefit ratio (of 5.45) was recorded in Spinosad 240SC, followed by imidacloprid 25%WP (992.33) with cost-benefit ratio (5.79). Among the botanical extracts, Neem leaf extract resulted in a yield of (685 kg/ha) with a cost-benefit ratio of (1.59) was recorded. It was concluded that all the tested insecticides were reducing the population of cabbage larvae and aphids. All the botanical extracts reduce the population of aphids and cabbage larvae, but as compared to other extracts neem extracts showed the best results among them. Hence using Imidacloprid 25% WP, Spinosad 240 SC at District Dadu is recommended for sustainable management of cabbage larvae and aphids.